Analysis of the medicinal potentials of cashew tree (Anacardium occidentale Linn): a brief review (Research, Society and Development, 2021)
Anacardium occidentale Linn, popularly known as cashew tree, is a plant species native to northeastern Brazil. Among its uses, medicinal can be highlighted in therapeutic and curative processes. The aim of this study is to discuss the medicinal potentials of cashew tree in popular medicine in the Northeast, analyzing its properties and main uses by the population. This is a brief review that used studies published between 2002 and 2020, available in the Google Scholar database, searches were made using the keywords “Anacardium occidentale L.”, “Anacardium occidentale L. caatinga”, “Anacardium occidentale L. etnobotânica” and “Anacardium occidentale L. medicinal”. Of the 30 selected works, 10 were elected according to inclusion criteria to compose the present article. Studies indicate potentials for treating and / or curing wounds, inflammations, infections and gastrointestinal problems, mainly due to properties derived from their secondary metabolites. In addition, there is a need for further studies focused on the theme, aiming at strengthening ethnobotanical research in Brazil.